On Teaching Im/Migration in an Undergraduate Classroom - Dhar, Amrita (Radical Teacher, 2021)
This article examines the urgencies, challenges, and rewards of teaching about migration, emigration, and immigration in our time of massive human movement across the globe. I describe and analyse the beginnings, structure, and takeaways from my undergraduate course on the literature of human movements (whether for reasons of refuge, asylum, choice, adventure, exploration, survival). I argue that despite growing collective acknowledgment of increasing human mobility across our planet, it is the power and wisdom of stories through which we best engage with the specific and multifaceted realities of persons losing home, making home, making other, and making own. I also suggest, from my classroom experience, that a slow, reflective, and immersed sharing of stories of those who have been displaced, misplaced, replaced, and strangely-placed is a key pedagogical aspect of discussing im/migration in the twenty-first century, and that especially in the United States, we owe it to ourselves and our students to know and interrogate the longer vocabularies and histories of othering and belonging in the English language. Through my discussion of the class activities and conversations, I show, similarly, the ways in which a literature class on the topic of im/migration functions also as a generative venue for intersectional considerations of race, gender, ethnicity, class, caste, disability, sexuality, nationality, and un/documented status. I also include reflections about future iterations of this course as I draw on summative comments from my students. Finally: although my pedagogy is informed by my own migrant status in the US, I offer means for pedagogues from a range of backgrounds and instructional levels to engage with and further this conversation in different parts of the world.